2018
DOI: 10.1016/j.ecoenv.2018.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Four selected high molecular weight heterocyclic aromatic hydrocarbons: Ecotoxicological hazard assessment, environmental relevance and regulatory needs under REACH

Abstract: Little is known about the ecotoxicity of heterocyclic aromatic hydrocarbons (NSO-HETs) to aquatic organisms. In the environment, NSO-HETs have been shown to occur in a strong association with their unsubstituted carbocyclic analogues, the polycyclic aromatic hydrocarbons (PAH), for which much more information is available. The present study addressed this issue by investigating the toxicity of four selected NSO-HETs in green algae (Desmodesmus subspicatus), daphnids (Daphnia magna) and fish embryos (Danio reri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…41,42 The aqueous solubility of BNF (0.25 ± 0.01 mg L −1 ) was also consistent with a literature value where the solubility of BNF was determined at 20 °C in Elendt M4 medium (described in OECD guideline 202) containing some inorganic salts (0.25 mg L −1 ). 43 The equilibrium kinetics of the measured S w are shown in Figure S1.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…41,42 The aqueous solubility of BNF (0.25 ± 0.01 mg L −1 ) was also consistent with a literature value where the solubility of BNF was determined at 20 °C in Elendt M4 medium (described in OECD guideline 202) containing some inorganic salts (0.25 mg L −1 ). 43 The equilibrium kinetics of the measured S w are shown in Figure S1.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…One data point was a C. dubia reproduction EC10 value of 1.16 µg/L (0.007 µmol/L) for 2‐hexylthiophene (ExxonMobil Biomedical Sciences [EMBSI], 2020a ). The other data point was a D. subspicatus growth rate NOEC value of 0.566 µg/L (0.002 µmol/L) for benzo[ b ]naphtha [2,1‐d]thiophene (Brendal et al, 2018 ). The excursion of 2 out of 37 data points below the HC5 is consistent with the 95% protection level goal (i.e., 94.6% [35/37]).…”
Section: Resultsmentioning
confidence: 99%
“…The HACs are more polar and subsequently more soluble than their homocyclic counterparts and can be bioavailable in environmental media. These compounds have been measured in a variety of environmental matrices, and studies have reported effects on aquatic organisms (Bleeker et al, 1998 ; Brendel et al, 2018 ; Dijkman et al, 1997 ; Peddinghaus et al, 2012 ). Presumably, due to their lower concentrations in the environmental in comparison with their homocyclic counterparts, these heterocyclic polycyclic aromatic compounds (PACs) are not considered to be risk drivers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In natural conditions, however, in presence of relevant solar radiation, a number of PAHs were found to be acutely toxic to aquatic organisms at concentrations that were similar to those tested in laboratory (Landrum et al 1984;Oris et al 1984), thus highlighting the importance of carrying out toxicological analyses in experimental conditions that are as similar as possible to those found in field. Also, the knowledge on ecotoxicity of NSO-HETs to aquatic plants is still rather scarce (Brendel et al 2018).…”
Section: Hydrocarbonsmentioning
confidence: 99%